Clinical analysis of single filtration plasmapheresis using continuous renal replacement therapy machines in kidney transplantation - Eunsoo Lim; Yujeong Kim; Jong Cheol Jeong; Inwhee Park; Heungsoo Kim; Su Hyung Lee; Chang-Kwon Oh; Gyu-Tae Shin (The Korean Society of Nephrology, 2017)
Background: Plasmapheresis has become an essential element of kidney transplantation (KT). In the present study, we report clinical outcomes of filtration plasmapheresis using continuous renal replacement therapy machines with a single filter for the first time in Korea. Methods: We retrospectively analyzed six patients who underwent filtration plasmapheresis for KT in our center; plasmapheresis was performed using the Plasmaflex (Baxter®) with a TPE 2000 filter set (Baxter®) in our hemodialysis unit. Five percent albumin was used as the replacement fluid, and intravenous immunoglobulin G was administered after each plasmapheresis session. The target preoperative ABO isoagglutinin titer was less than 1:8. Results: Filtration plasmapheresis was performed in four patients for ABO-incompatible KT, one for antibody-mediated rejection after KT, and the last one for positive T cell crossmatch. Altogether, 46 sessions of plasmapheresis were performed. ABO isoagglutinin titers successfully declined to or below the target level in all patients, and all patients successfully received KT with no significant antibody titer rebound. Acute antibody-mediated rejection and positive T cell crossmatch were well treated with filtration plasmapheresis, and no patient required fresh frozen plasma infusion for coagulopathy. There were one episode of hypotension and three of hypocalcemia. No patients experienced bleeding, infection, or allergic reaction. Conclusion: Filtration plasmapheresis was effective and safe. Although our result is from a single center, our protocol appears to be promising.